ORGANIZATION AND PRINCIPLES IN THE PROCESS OF CURRICULUM FOR EARLY CHILDHOOD EDUCATION UNITS OF THE SECRETARIA OF BELEM MUNICIPAL-PARA-BRAZIL: A NEW WORK PROPOSAL (Fiep Bulletin - online, 2011)
The pedagogical practice developed in some units of Early Childhood Education Department of Education Department of Bethlehem is aimed at development of children through learning situations based on the social context in which they are embedded, to promote a welcoming and safe environment that is conducive to the expansion their knowledge. For this achievement, it takes into account the need for the movement of multiple languages, experiencing diverse experiences of the agents of change and giving opportunities through the findings of conversation, storytelling, paintings, drawings, models, cutting and pasting, music, games and jokes general. Thus is born a curriculum that emerges from this movement languages that allow generating the children perform the actions, interactions, expand their knowledge, learning and skills inherent in being a socially developed.
Keywords: Curriculum; Multiple Languages; Learning